Ginkgo biloba Responds to Herbivory by Activating Early Signaling and Direct Defenses - Mohanta, Tapan Kumar; Occhipinti, Andrea; Atsbaha Zebelo, Simon; Foti, Maria; Fliegmann, Judith; Bossi, Simone; Maffei, Massimo E.; Bertea, Cinzia M. (PLOS ONE, 2012)
Background Ginkgo biloba (Ginkgoaceae) is one of the most ancient living seed plants and is regarded as a living fossil. G. biloba has a broad spectrum of resistance or tolerance to many pathogens and herbivores because of the presence of toxic leaf compounds. Little is known about early and late events occurring in G. biloba upon herbivory. The aim of this study was to assess whether herbivory by the generalist Spodoptera littoralis was able to induce early signaling and direct defense in G. biloba by evaluating early and late responses. Methodology/Principal Findings Early and late responses in mechanically wounded leaves and in leaves damaged by S. littoralis included plasma transmembrane potential (Vm) variations, time-course changes in both cytosolic calcium concentration ([Ca2+]cyt) and H2O2 production, the regulation of genes correlated to terpenoid and flavonoid biosynthesis, the induction of direct defense compounds, and the release of volatile organic compounds (VOCs). The results show that G. biloba responded to hebivory with a significant Vm depolarization which was associated to significant increases in both [Ca2+]cyt and H2O2. Several defense genes were regulated by herbivory, including those coding for ROS scavenging enzymes and the synthesis of terpenoids and flavonoids. Metabolomic analyses revealed the herbivore-induced production of several flavonoids and VOCs. Surprisingly, no significant induction by herbivory was found for two of the most characteristic G. biloba classes of bioactive compounds; ginkgolides and bilobalides. Conclusions/Significance By studying early and late responses of G. biloba to herbivory, we provided the first evidence that this “living fossil” plant responds to herbivory with the same defense mechanisms adopted by the most recent angiosperms.